The Media and Public Agendas Testing for Media Effects in Argentina During 2003-2008 - Cuestas, Juan Carlos (2009)
In this paper we examine the presence of agenda-setting effects by the print media in Argentina from June 2003 to December 2008. Using previously unavailable monthly data on newspapers mentions we test two hypotheses about the relationship between the different agendas. We find support for the hypothesis that there were media effects during our period of analysis. More specifically, we find that the total number of newspaper mentions of the President positively influenced public confidence in the government. Finally, there is also evidence of a strong and stable relationship between the total number of economic news and leading economic indicators.